Cournot equilibrium with free entry for capitalistic and workers' enterprises - Pinhas, David. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1985., 1985)
The purpose of this dissertation is to determine the Cournot Equilibrium with Free Entry for Capitalistic and Workers' Enterprises. An alternative Cournot-like free entry notion to Novshek's CEFE which we call Cournot-Sertel Equilibrium, is used to accomplish our purpose. Our analysis is carried out in a model such that potential firms all producing a homogeneous good possess identical workers and a common technology where preferences and production functions follow the functional forms of the log-linear model developed previously by Sertel. Making use of Cournot-Sertel Equilibrium concept; the size of the oligopoly, the production level, the capital and labor jnputs of each firm, the number of workers in each firm, total output of the industry and the price of the good are determined at equilibrium for profitmaximizing firms, for util ity maximizing workers' enterprises and for the first time for an industry where both coexist. Furthermore, it is demonstrated that Cournot-Sertel Equilibrium is also Novshek's CEFE for capitalistic and workers' enterprises in a log-linear model.
Keywords: Oligopolies.; Equilibrium (Economics)